Perceptions about HIV pre-exposure prophylaxis among healthcare professionals in Spain (PERPPRES Study) - Javier Sánchez-Rubio Ferrández; José Manuel Martínez Sesmero; Herminia Navarro Aznárez; Sergio Fernández Espínola; Ismael Escobar Rodríguez; José Manuel Ventura Cerdá (Farmacia Hospitalaria)
Objective: To determine the level of support, knowledge and perceptions of pre-exposure prophylaxis (PrEP) by Infectious Disease Specialists and Hospital Pharmacists in Spain. Methods: Cross-sectional study through an on-line 31-item survey (sociodemographical data, employment status/experience, knowledge of PrEP, use, identified barriers and economic issues). A univariate analysis was performed to evaluate the variables associated with support for PrEP, and compare the assessments by Specialists and Pharmacists. The questions about support for PrEP and agreement with the indication approval were repeated after showing data from published studies. The significance of the change in the answers was analyzed using the McNemar Test. Results: 211 questionnaires were received (80.1% from Pharmacists). 40.3% had low/no familiarity with PrEP (46.2% Pharmacists vs. 16.7% Physicians; p < 0.01). A 53.6% of them would support the use of PrEP (49.7% Pharmacists vs. 69% Physicians; p = 0.038). The minimum acceptable efficacy in order to support PrEP was 85.0 ± 15.5% (82.6 ± 12.1% by Physicians vs. 85.6 ± 15.0% by Pharmacists; p = 0.02). The variables associated with support were: medical profession (OR = 2.26; 95%CI 1.1-4.6; p = 0.038) and lower demand for efficacy (difference = 10.5%; 95%CI 6.9 to 14.1; p < 0.001). After receiving the information, there was an increase in their support for use and indication approval. Most participants (81.5%) did not support its reimbursement. The main barriers identified were: an increase in risk behaviour (24.1%), increase in sexually transmitted diseases (19.0%), resistance (16.6%) and cost (16.0%). Conclusions: More than half of participants were familiar with PrEP. The majority of them would support its use and the approval of the indication, but would not reimburse it. The use of PrEP in real practice is currently low.